The importance and proper management of diuretics in clinical medicine: a pharmacological approach (Research, Society and Development, 2022)
Diuretics are drugs that increase the volume of urinary excretion. Generally, they inhibit renal transport of ions and reduce sodium reabsorption in different portions of the nephron, consequently the eliminated ions are concentrated in greater amounts together with water. Therefore, these substances increase urine output, often alter its pH, as well as the ionic arrangement of urine and blood. The following objective was to describe, through a narrative review of the literature, the main aspects of each class of diuretics and the specific clinical conditions for their administration. The applicability of the different classes is according to the increase in sodium secretion. Loop diuretics are considered the most potent, followed by thiazides. The other classes are used either in combination to promote additional diuresis, to preserve a given condition, or to be better suited to a specific comorbidity. Diuretics are indicated in conditions that require normalization of abnormal fluid retention, edema, or management of hypertension.